The Effect of Intensity of Religious Activities and Social Environment on Juvenile Delinquency Behavior in Early Adolescence Phase Tahfiz Program Students - Jadmiko Aji Saputro; Fajhri Prima Vandhi; Antony Mahendra; Muhammad Alfi Syahrin (Educational Research Center, 2026)
This study aims to analyze the influence of religious activity intensity and peer environment on juvenile delinquency among early adolescence students enrolled in a tahfiz program. The study employed a quantitative correlational design. The population consisted of 87 fifth- and sixth-grade tahfiz students at Sekolah Alam Insan Mulia Surabaya, with 32 students selected through purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire and analyzed through multiple linear regression using SPSS. The results indicated that the intensity of religious activities had a significant negative effect on juvenile delinquency (β = -1.136; p < 0.05), suggesting that higher participation in religious activities is associated with lower levels of delinquent behavior. Meanwhile, the peer environment showed a positive but statistically insignificant effect on juvenile delinquency (β = 0.440; p > 0.05). Simultaneously, religious activity intensity and peer environment significantly influenced juvenile delinquency (F = 11.290; p < 0.05), with a coefficient of determination of 43.8%. These findings suggest that strengthening religious activities plays an important role in reducing juvenile delinquency, while the peer environment requires positive social support to contribute effectively to adaptive behavioral development among early adolescence students.